2002
DOI: 10.1034/j.1398-9995.2002.23687.x
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Interleukin 16 (IL‐16) in children with atopic/eczema dermatitis syndrome (AEDS): a novel serological marker of disease activity

Abstract: We suggest that IL-16 could serve as a useful marker of disease activity in childhood pAEDS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
26
1
2

Year Published

2004
2004
2011
2011

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 35 publications
5
26
1
2
Order By: Relevance
“…It is possible that IL-16 secreted from peripheral eosinophils may accelerate chronic inflammation at the nasal mucosa by activating T lymphocytes and eosinophils themselves in allergic rhinitis. However, several reports have shown that circulating IL-16 is produced mainly from T cells at the inflammatory site in allergic disease with eosinophilia [6, 23]. It remains unclear which source of IL-16 primarily contributes to pathogenesis in allergic rhinitis.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that IL-16 secreted from peripheral eosinophils may accelerate chronic inflammation at the nasal mucosa by activating T lymphocytes and eosinophils themselves in allergic rhinitis. However, several reports have shown that circulating IL-16 is produced mainly from T cells at the inflammatory site in allergic disease with eosinophilia [6, 23]. It remains unclear which source of IL-16 primarily contributes to pathogenesis in allergic rhinitis.…”
Section: Discussionmentioning
confidence: 99%
“…In acute skin lesions, the predominance of Th2 lymphocytes that produce IL-4 and IL-13 is replaced by Th1 lymphocytes with predominant IFN-γ production in the chronic phase of AD [9,12]. Previous studies also demonstrated impaired Th1 and dominant Th2 cytokine expression in both CD4+ and CD8+ T cells in peripheral blood of AD patients [8].…”
Section: Discussionmentioning
confidence: 92%
“…Among chemotactic factors, interleukin (IL)-16 has been fully characterized as an immunomodulatory cytokine, playing a role in the recruitment of CD4-expressing Th cells, monocytes and eosinophils to the site of inflammation. Besides its chemotactic properties, IL-16 can trigger IL-2 receptor α-chain expression and activate CD4+ T cells in synergy with IL-2 or IL-15 [9]. In addition, IL-16 amplifies the inflammatory reactions by stimulating cytokine production in monocytes and maturing macrophages [10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The high expression of CD86 on B cells in AD (72) might provide costimulatory signals via CD28 on T cells, resulting in the production of large amounts of IL-5 and IL-13 in AD (73). Moreover, activated B cells produce the chemokines CCL17 (TARC), CCL22 (MDC) and IL-16 and thus may recruit other immune cells into the skin (74,75). The depletion of B cells with rituximab, an anti-CD20 antibody, resulted in a rapid reduction in skin inflammation in all patients with a sustained effect over 5 months in five of six patients (76).…”
Section: Targeting B Cells and Igementioning
confidence: 99%